Mesa redonda: Técnicas alternativas a las transfusiones perioperatorias - Reyes O. , Carlos; Baron, Jean F.; Pedemonte, Oneglio; Hoffman , Celia; Retamales, Avelino (Revista Hospital Clínico Universidad de Chile, 2000)
Resumen no disponible